2018
DOI: 10.1159/000492494
|View full text |Cite
|
Sign up to set email alerts
|

MPT0B169 and MPT0B002, New Tubulin Inhibitors, Induce Growth Inhibition, G2/M Cell Cycle Arrest, and Apoptosis in Human Colorectal Cancer Cells

Abstract: We previously synthesized new tubulin inhibitors, MPT0B169 and MPT0B002, which induced growth inhibition and apoptosis in leukemia cells. However, their effects on solid tumor cells have not been determined. In this study, we investigated the effects of MPT0B169 and MPT0B002 on glioblastoma, breast, lung, and colorectal cancer (CRC) cell lines. A cell viability analysis showed that MPT0B169 and MPT0B002 were more effective in inhibiting the proliferation of COLO205 and HT29 CRC cells than U87MG and GBM8401 gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Interfering with α-tubulin or β-tubulin expression causes G2-M cell cycle arrest due to disrupted microtubule dynamics [19][20] . The same results were obtained after disruption of tubulin polymerization by the addition of speci c chemical agents to the animal cell culture medium, which was accompanied by apoptosis [21][22] . Overexpression of tubulin-associated RITA decreased the levels of cyclin D1, cyclin E, CDK2, HES-1, and NF-kappaB p65, resulting in growth inhibition and inducing G0-G1 phase arrest in SMMC7721 and HepG2 cells [23] .…”
Section: Discussionsupporting
confidence: 66%
“…Interfering with α-tubulin or β-tubulin expression causes G2-M cell cycle arrest due to disrupted microtubule dynamics [19][20] . The same results were obtained after disruption of tubulin polymerization by the addition of speci c chemical agents to the animal cell culture medium, which was accompanied by apoptosis [21][22] . Overexpression of tubulin-associated RITA decreased the levels of cyclin D1, cyclin E, CDK2, HES-1, and NF-kappaB p65, resulting in growth inhibition and inducing G0-G1 phase arrest in SMMC7721 and HepG2 cells [23] .…”
Section: Discussionsupporting
confidence: 66%
“…The biological functions of normal cells experience major changes during carcinogenesis to promote the progression of cancer, including invasion and metastasis (31,32). Various tissue cells in an organism maintain a quantitative balance through proliferation and apoptosis, however, disturbing this balance leads to diseases such as cancer (33,34). Apoptosis is the main mechanism of cell death induced by various anticancer drugs, thus, the role of apoptosis in cancer therapy has become a focus in antitumor research (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained clearly showed that PTC‐028 induced the accumulation of cells at the G2/M phase (Figure 4A). The disruption of tubulin assembly was previously shown to induce cell cycle arrest at the G2/M phase in cancer cells 24‐26 …”
Section: Resultsmentioning
confidence: 99%